O trabalho docente representado por estagiárias do Curso Normal em textos de autoconfrontação simples - Oliveira, Carlos Héric Silva (2016)
This thesis aims at investigating the representations the trainees construct of themselves and of their work as future teachers during a situation of supervised training in direct self-confrontation texts which occur in the context of initial training of the Elementary School Teaching Course teachers. Thereby, we intend to analyze how the trainees‟ representations occur during the supervised training through development in the context of teaching. To carry out this research, we used the theoretical-methodological assumptions of the Socio-discursive Interactionism (hereinafter ISD) – whose main representative is Bronckart (1999/2012, 2006, 2008) – comprising human action and the discursive action as development units among human beings who represent their acts through language, taking into consideration that the trainees mobilize their knowledge, in their teaching practice, endorsing Vanhulle‟s theories (2009, 2014). Another theoretical-methodological current is that of Labor Studies, of which, particularly, we will use the Activity Clinic (CLOT, 2007, 2010; FAÏTA, 2000) and the Activity Ergonomics (AMIGUES, 2004; DEJOURS, 2004; SAUJAT, 2004). When studying the representations of the trainees‟ work, we found that the texts produced by the trainees in the interviews in simple self-confrontation (hereinafter EACs) show representations of the physical and socio-subjective worlds capable of contributing to the development and initial training of the teachers attending The Elementary School Teacher Training Course, as well as that of the teachers of other undergraduate programs which put the student in a situation of development with professional practice. It is for this reason that we used the text analysis model proposed by Bronckart (1999/2012), developed in ISD studies, to conduct our analyses. Data production occurred in a school in the state of Sergipe whose focus concentrated in the Fundamental School Teacher Training Course, one high school modality that professionalizes future teachers to teach the early grades of Elementary School. To compose the corpus of the research, four EACs were recorded with each trainee with the researcher, totalizing eight meetings. In this sense, our data were constructed from the EACs texts produced by the trainees on internship work situation. The results showed that the teachers‟ representations occurred in situations of internship where they were acting professionally, which each trainee has during the training, as well as in the different situations of the physical, socio-subjective worlds that are represented through social roles. Another relevant point in the results indicates the mobilization that happens between the representations – characteristics of the educational context under the aspect of teacher training – capable of offering the trainees conditions to reflect, to act and transform their work. In relation to their knowledge mobilized in the activity, we perceive that the trainees use the theoretical knowledge as guidelines for their teaching aiming the professional practice know-how through experiential knowledge acquired in the educational context, both before and during their training